2021
DOI: 10.9734/jpri/2020/v32i4731113
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of an Emerging Therapy against COVID-19: Is Convalescent Plasma a Hidden Gem Not Yet Optimized?

Abstract: Background: An unprecedented global effort in identifying potentially viable and emerging drugs for effective treatment of the novel coronavirus disease (2019) is being made. Of the most promising candidate therapies, convalescent plasma (CP), albeit controversial, is approved for emergency use authorization (EUA) by the U.S. Food and Drug Administration (FDA). The concept rests on passive immunity, achieved by administering plasma with high titers of neutralizing antibodies to reduce severity of SARS-CoV-2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Serious COVID-19, including severe and critical types, is usually characterized by severe respiratory disease, multiple organ dysfunction, immune cell exhaustion, and local or systemic hyperinflammation. [31][32][33] In this period, the pathophysiologic damage to the body derives more from the host's own immune system rather than from the virus itself. Consequently, immunomodulatory treatment becomes pertinent.…”
Section: Discussionmentioning
confidence: 99%
“…Serious COVID-19, including severe and critical types, is usually characterized by severe respiratory disease, multiple organ dysfunction, immune cell exhaustion, and local or systemic hyperinflammation. [31][32][33] In this period, the pathophysiologic damage to the body derives more from the host's own immune system rather than from the virus itself. Consequently, immunomodulatory treatment becomes pertinent.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found improved clinical outcomes and higher extubation rates in hospitalized Covid-19 patients with ARDS in the ICU. In addition, they provided anti-coagulant properties in patients presented with DIC, thrombotic microangiopathy, and MODS [38]. Hypotension is the most common adverse effect of TPE.…”
Section: Cpfa In Critically Ill Covid-19mentioning
confidence: 99%